2021
DOI: 10.1590/s0004-2803.202100000-93
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Endoscopic Balloon Dilation in Iranian Pediatric Patients With Esophageal Stricture

Abstract: BACKGROUND: Esophageal stenosis (ES) in children is a fixed intrinsic narrowing of the esophagus due to numerous aetiologies. OBJECTIVE: This study aimed to determine the clinical and nutritional impacts of endoscopic balloon dilation (EBD) in Iranian children with an esophageal stricture. METHODS: This retrospective study, pediatric patients (aged <18 years) who underwent EBD for esophageal stricture from April 2015 until March 2020 in Abuzar Children’s Hospital (Ahvaz, Iran) were enrolled in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In our study, about 47% of patients had symptom relief after their first ED session, comparable to the rates achieved by others. [7,14] The rest, 52.4%, had multiple sessions. We observed that a median of 2 sessions was required for patients with multiple ED.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, about 47% of patients had symptom relief after their first ED session, comparable to the rates achieved by others. [7,14] The rest, 52.4%, had multiple sessions. We observed that a median of 2 sessions was required for patients with multiple ED.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several methods including balloon dilation and Savary dilator were used more frequently in the treatment of esophageal stenosis. 2,3 Endoscopic electrocautery incisional therapy (EIT) is the method that is recommended for refractory esophageal stricture especially anastomotic stricture. We discuss the first report of endoscopic electrocautery surgery for the child with refractory anastomotic stricture.…”
Section: Introductionmentioning
confidence: 99%